Student Needs Assessment Strategy in Islamic Group Counseling Services - Lestari, Kartika; Hartini, Hartini; Sumarto, Sumarto; Pankham, Sumaman; Aciu, Lia Elena (Edumulti: Jurnal Rumpun Ilmu Pendidikan Multidisiplin, 2025)
This study aims to explain the management strategy for assessing the needs of grade VIII students in planning Islamic group counseling services at SMP IT Cahaya Robbani Kepahiang. The background of this research is based on the importance of structured needs assessment as a basis for designing counseling guidance services that are relevant to student development. The research method used is a qualitative descriptive approach with a case study design. Data was collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman analysis model which included data reduction, data presentation, and conclusion drawn. The results of the study show that the management of student needs assessment is carried out in a planned manner through three main stages: planning, implementation, and analysis of assessment results. Needs data were obtained through surveys, observations, and interviews, and then used as a basis for designing Islamic value-based group counseling programs. This strategy has proven effective in directing counseling services to align with the real needs of students, while strengthening their involvement and spiritual awareness in dealing with personal and social problems. Research confirms that a good and structured needs assessment is essential in the development of contextual and meaningful Islamic counseling services for students. The recommendation of this study is that schools should continuously integrate needs assessment in counseling guidance programs, improve the competence of BK teachers in an Islamic approach, and develop an Islamic value-based counseling model that is adaptive to the dynamics of student needs.